Get the answers you need at Westonci.ca, where our expert community is always ready to help with accurate information. Get immediate and reliable answers to your questions from a community of experienced experts on our platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
To solve the system of equations:
[tex]\[ \begin{aligned} y &= 6x - 8 \\ y &= 4x + 6 \end{aligned} \][/tex]
we need to find a common solution [tex]\((x, y)\)[/tex] that satisfies both equations simultaneously.
### Step-by-Step Solution:
1. Set the equations equal to each other:
Since both equations are equal to [tex]\(y\)[/tex], we can set the right-side expressions of both equations equal to each other.
[tex]\[ 6x - 8 = 4x + 6 \][/tex]
2. Isolate the variable [tex]\(x\)[/tex]:
To find the value of [tex]\(x\)[/tex], we start by isolating [tex]\(x\)[/tex] on one side of the equation.
Subtract [tex]\(4x\)[/tex] from both sides:
[tex]\[ 6x - 4x - 8 = 4x - 4x + 6 \\ 2x - 8 = 6 \][/tex]
Then, add 8 to both sides:
[tex]\[ 2x - 8 + 8 = 6 + 8 \\ 2x = 14 \][/tex]
Finally, divide both sides by 2:
[tex]\[ x = \frac{14}{2} = 7 \][/tex]
3. Substitute [tex]\(x = 7\)[/tex] back into one of the original equations:
We can use either equation to find the value of [tex]\(y\)[/tex]. Let's use the first equation:
[tex]\[ y = 6x - 8 \][/tex]
Substitute [tex]\(x = 7\)[/tex]:
[tex]\[ y = 6(7) - 8 \\ y = 42 - 8 \\ y = 34 \][/tex]
So, the solution to the system of equations is:
[tex]\[ x = 7 \][/tex]
[tex]\[ y = 34 \][/tex]
[tex]\[ \begin{aligned} y &= 6x - 8 \\ y &= 4x + 6 \end{aligned} \][/tex]
we need to find a common solution [tex]\((x, y)\)[/tex] that satisfies both equations simultaneously.
### Step-by-Step Solution:
1. Set the equations equal to each other:
Since both equations are equal to [tex]\(y\)[/tex], we can set the right-side expressions of both equations equal to each other.
[tex]\[ 6x - 8 = 4x + 6 \][/tex]
2. Isolate the variable [tex]\(x\)[/tex]:
To find the value of [tex]\(x\)[/tex], we start by isolating [tex]\(x\)[/tex] on one side of the equation.
Subtract [tex]\(4x\)[/tex] from both sides:
[tex]\[ 6x - 4x - 8 = 4x - 4x + 6 \\ 2x - 8 = 6 \][/tex]
Then, add 8 to both sides:
[tex]\[ 2x - 8 + 8 = 6 + 8 \\ 2x = 14 \][/tex]
Finally, divide both sides by 2:
[tex]\[ x = \frac{14}{2} = 7 \][/tex]
3. Substitute [tex]\(x = 7\)[/tex] back into one of the original equations:
We can use either equation to find the value of [tex]\(y\)[/tex]. Let's use the first equation:
[tex]\[ y = 6x - 8 \][/tex]
Substitute [tex]\(x = 7\)[/tex]:
[tex]\[ y = 6(7) - 8 \\ y = 42 - 8 \\ y = 34 \][/tex]
So, the solution to the system of equations is:
[tex]\[ x = 7 \][/tex]
[tex]\[ y = 34 \][/tex]
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.